Anterior suprachoroidal hemorrhage abutting anterior chamber intraocular lens - Shakarchi, Fatma; Starr, Matthew R. (Digital Journal of Ophthalmology, 2026)
An 88-year-old man presented at the Mayo Clinic Department of Ophthalmology with a large suprachoroidal hemorrhage following a complicated lens exchange with anterior chamber intraocular lens (ACIOL) placement. The choroidal hemorrhages were appositional and abutting the ACIOL, painless, with a formed anterior chamber. The patient was hypermetropic and had an intraocular pressure of 23 mm Hg, which was controlled with dorzolamide/timolol drops at the time of presentation. He was managed conservatively with topical therapy for 17 days (prednisolone acetate 1% 6 times daily and atropine 0.01% twice daily), followed by choroidal drainage surgery with warfarin cessation (which he was using for atrial fibrillation). Postoperatively, he refracted to 20/80 while retaining his ACIOL and successfully resumed warfarin without hematologic complications at the 1-year postoperative visit with complete resolution of the choroidal hemorrhages.